Analysis of Sharia Compliance in the Implementation of Hajj Saving Product - Sulvariany Tamburaka; Nitri Mirosea; Hendriawan Hendriawan (International Journal of Religious and Cultural Studies, 2021)
This study aims to investigate the implementation of sharia compliance of a hajj saving product. The data analysis method used was descriptive analysis with quantitative approach. The data collection method employed was open questionnaire and documentation.The result shows that Hajj saving product of BNI Baitullah IB Hasanah was in accordance to guideline of Syariah principles namely: Justice, Balance (al ‘adl wa tawazzun), Security (al maslahah), Universalism, and free of gharar and riba. Hajj saving of BNI Baitullah IB Hasanah is based on two agreements namely (1)wadiah yad dhamanah which means that the form of depositing funds between the owner of the fund and the recipient of the deposit that is trusted to safeguard the funds; and secondly (2) mudharabah mutlaqah, which is an agreement between capital owners and the bank whereas the funds deposited in the bank is managed and distributed to those who needs fund.